1980
DOI: 10.3109/00365528009181445
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Concentrations of Pancreatic Enzymes following Pancreatic Replacement Therapy

Abstract: The activities of amylase, lipase, phospholipase, and trypsin in four commercially available preparations of pancreatin with different galenic and adjunctive protective properties were estimated in vitro, using human small-intestinal juice as the incubation medium. These preparations were administered to healthy subjects and to patients with severe pancreatic insufficiency, and their ability to increase the intestinal concentrations of pancreatic enzymes was evaluated. The relations between in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Pan creatic enzyme therapy certainly increases the intraluminal concentration of pancreatic enzymes in patients with chronic pancreati tis [35,48], However, even intense substitu tion with pancreatic enzymes neither nor malizes the enzyme concentrations in the small intestine nor the total fat absorption from the intestine [35], Consequently, it is still debatable if there is any place for en zyme substitution in patients with moder ately decreased exocrine pancreatic function and slight steatorrhoea. It seems reasonable to reserve the enzyme substitution to cases with notable pancreatogenous steatorrhoea, say patients with more than 20 g fat in the stools per day.…”
Section: Pancreatic Enzyme Therapymentioning
confidence: 99%
“…Pan creatic enzyme therapy certainly increases the intraluminal concentration of pancreatic enzymes in patients with chronic pancreati tis [35,48], However, even intense substitu tion with pancreatic enzymes neither nor malizes the enzyme concentrations in the small intestine nor the total fat absorption from the intestine [35], Consequently, it is still debatable if there is any place for en zyme substitution in patients with moder ately decreased exocrine pancreatic function and slight steatorrhoea. It seems reasonable to reserve the enzyme substitution to cases with notable pancreatogenous steatorrhoea, say patients with more than 20 g fat in the stools per day.…”
Section: Pancreatic Enzyme Therapymentioning
confidence: 99%
“…With granulated preparations, higher en zyme activities reach the small intestine than with tablets [27], Detailed studies comparing the effect of increasing the quantity of lipase are not available. Preliminary studies showed that with the common American medication of 10,000-12,000 lipase units per meal, a 50% reduction in steatorrhoea was achieved.…”
Section: Choice O F Enzyme Preparationmentioning
confidence: 99%
“…1, 2). I. Ihse et al [31] доказали в исследовании, соответствующем уровню В, что при приеме таблетированных ферментных препаратов не увеличивается содержание панкреатических ферментов в дуоденальном аспирате в течение 2 часов после пробного завтрака. Аналогично этому таблетированные препараты с таниновой оболочкой, то есть защищенные от низкого рН и пепсина, также не способствовали изменению уровня ферментов ПЖ в кишечном содержимом.…”
unclassified